NETWORKING AS A FORM OF INTERNATIONALIZATION IN EDUCATION: CASE STUDY OF KNRTU - Anna S. Sukhristina; Julia N. Ziyatdinova; Alexandr M. Kochnev (Высшее образование в России, 2016)
The paper describes international academic cooperation in networking format. The paper is focused on the development of a networking model that is to facilitate international relations in education. The authors demonstrate effectiveness of the model and describe the steps of establishing the representative office of the Russian engineering university in Vietnam.